The effectiveness of trivariate shrinkage computer radiography (CR) technique on image quality and anatomical information in radiotherapy geometric verification - Cristian NP, Arpan Doli; Latifah, Leny; Rusyadi, Luthfi (Universitas 'Aisyiyah Yogyakarta, 2023)
Geometric verification is mandatory before radiotherapy treatment by comparing the image suitability results from the Computer Radiography (CR) imaging portal with the planned reference image at the TPS (Treatment Planning System). EPID is an advanced technology that has yet to be applied to all radiotherapy departments in Indonesia because it is commercial, so CR is an alternative to geometric verification. The purpose of analyzing the effectiveness of using the Denoising Technique with Trivariate Shrinkage CR compared to EPID in improving image quality and anatomical information on geometric radiotherapy verification. Research Method experimental quasy or pseudo experiment with pretest and posttest design of one group with control design. The respondents were all patients who underwent CR and EPID examinations. Determination of respondents using consecutive sampling so that the number of samples obtained was 16 samples. Denoising was performed using the Matlab Program with Trivariate Shrinkage on CR and compared to EPID. There are differences in anatomical information of geometric verification of radiotherapy carried out before and after denoising using Trivariate Shrinkage, as seen from all variables obtained p-value <0.05. There is no difference in anatomical information of geometric verification of radiotherapy denoising using Trivariate Shrinkage on CR compared to EPID, as seen from the variable obtained p-value >0.05. In conclusion, the Trivariate Shrinkage Computer Radiography (CR) technique effectively improves image quality and anatomical information in the geometric verification of radiotherapy. The Trivariate Shrinkage Computer Radiography (CR) technique can produce optimal images and provide good anatomical information comparable to EPID.Â Â Â